[Kr]4d104f13, The final layzer quenched configuration for highly charged ions. (September 2022) - Li, M.C.; Zhu, G.L.; Wang, K.; Si, R.; Chen, C.Y.; Brage, T.; Hutton, R.
Highlights: We have performed calculations of the ground state fine-structure energy for high Z members of the Praseodymium isoelectronic sequence. These are 59-electron systems, and our calculations were made possible by electron re-arrangement for the high-Z members to a [Kr]4 d 10 4 f 13 2 F configuration, which is Layzer-quenched, i.e., the electron correlation is minimal. We have used three different formulations to calculate the self-energy part of the QED correction to the fine-structure energy. Abstract: We discuss the Layzer quenched ground state configuration of [Kr] 4 d 10 4 f 13 along the Praseodymium (Pr) isoelectronic sequence between 80 ≤ Z ≤ 100 . The 2 F fine structure energy is examined from the point of view of the various contirbutions: correlation, frequency-independent and dependent Breit interaction and the two QED terms, self energy and vacuum polarisation. We find the fine structure energy to be dominated by the frequency-independent Breit interaction, correlation is relatively small, which is to be expected for this Layzer-quenched term. We also calculate the self energy using three different formulations, all included in the new version of the GRASP2K codes.